Efficacy of lipid lowering drug treatment for diabetic and non-diabetic patients: metaanalysis of randomised controlled trials. Issue 7550 (3rd April 2006) - Costa, João; Borges, Margarida; David, Cláudio; Carneiro, António Vaz
Abstract: Objective To evaluate the clinical benefit of lipid lowering drug treatment in patients with and without diabetes mellitus, for primary and secondary prevention. Design Systematic review and meta-analysis. Data sources Cochrane, Medline, Embase, and reference lists up to April 2004. Study selection Randomised, placebo controlled, double blind trials with a follow-up of at least three years that evaluated lipid lowering drug treatment in patients with and without diabetes mellitus. Data extraction Two independent reviewers extracted data. The primary outcome was major coronary events defined as coronary heart disease death, non-fatal myocardial infarction, or myocardial revascularisation procedures. Results Twelve studies were included. Lipid lowering drug treatment was found to be at least as effective in diabetic patients as in non-diabetic patients. In primary prevention, the risk reduction for major coronary events was 21% (95% confidence interval 11% to 30%; P < 0.0001) in diabetic patients and 23% (12% to 33%; P = 0.0003) in non-diabetic patients. In secondary prevention, the corresponding risk reductions were 21% (10% to 31%; P = 0.0005) and 23% (19% to 26%; P ≤ 0.00001). However, the absolute risk difference was three times higher in secondary prevention. When results were adjusted for baseline risk, diabetic patients benefited more in both primary and secondary prevention. Blood lipids were reduced to a similar degree in both groups. Conclusions The evidence that lipid lowering drug treatment (especially statins) significantly reduce cardiovascular risk in diabetic and non-diabetic patients is strong and suggests that diabetic patients benefit more, in both primary and secondary prevention. Future research should define the threshold for treatment of these patients and the desired target lipid concentrations, especially for primary prevention.